Assessing process, content, and politics in developing the global health sector strategy on sexually transmitted infections 2016-2021: Implementation opportunities for policymakers. - Andy Seale; Nathalie Broutet; Manjulaa Narasimhan (PLoS Medicine)
Andrew Seale and colleagues discuss the development of a global strategy to counter sexually transmitted infections.